Profitability Moderate The Effect Of Firm’s Characteristic On Capital Structure - Pancawati Hardiningsih, R.M. Oktaviani, Ceacilia Srimindarti, Firdaus Damas Septio Ardiansyah, (Jurnal Akuntansi, 2019)
The objective of this study is to examine and analyze the influence of the asset structure and the company size on the capital structure with profitability as a moderating variable. Company managers must make an efficient comparison between internal and external capital to maximize the benefits. The populations of this study areproperty and real estate companies which were listed in Indonesia stock exchange. The sample selection use purposive sampling method. The criteria which used for sampling were: (1) publishing financial statement; (2) make a profit; (3) holding data on asset structure and profitability; (4) using rupiah. The analysis tool usedin this research is PLS. The result of this study showed that asset structure and company size had a positive influence on the capital structure. Profitability moderate the influence of asset structure on the capital structure, and moderate the influence of the company size on a capital structure.